Os poemas de Manoel de Barros na perspectiva da linguística textual - Silva, Jaqueline Melo de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective within this work is to analise four poems from the author Manoel de Barros from the perspective of Textual Linguistics. The principal goal is to see the elaboration of cohesion and coherence factors in the poet's work. After the analisys, the study verify that many aspects, both in cohesion and in coherence, replay in most of the author's poems. Specially in the case of cohesion, the presente work observed the constance of repetitions of the ideas expressed at the poems. In the case of coherence, this study verify that it is done, at Manoel de Barros's work, mostly throughout the continuous questioning about the reader's knowledge of the word. Within the results, after observing the features adopted by the poet in order to develop the poems meanings, this study shows the importance of this kind of look upon Manoel de Barros's work. This type of view implicated a contribution to the lyrical text and to the interpretation of the entire author's work

O presente Trabalho de Conclusão de Curso traz uma análise de quatro poemas de Manoel de Barros sob a perspectiva da Linguística Textual, tendo como principal foco a formulação da coesão e da coerência dentro da obra do poeta. O estudo constatou algumas recorrências na obra do poeta, de forma que muitas características, tanto da coesão quanto da coerência, se repetem na maioria dos poemas. Particularmente em relação à coesão, este trabalho identificou o emprego constante de repetições, tanto na referenciação, quanto na sequenciação das ideias expressas nos poemas. Sobre a coerência, o presente estudo verificou que, nos poemas de Manoel de Barros, é feita, em geral, por meio do frequente questionamento do conhecimento de mundo do leitor. Ao observar os recursos adotados pelo poeta para construir os sentidos do texto, este trabalho evidencia a riqueza textual das construções poéticas de Manoel de Barros e busca contribuir para uma interpretação mais aprofundada da obra do poeta
Keywords: Barros, Manoel de 1916-2014; Linguística; Poesia; Coesão (Linguistica); Linguistics